Long term performance of an archored diaphragm wall embedded in stiff clay - 373176 Carswell, I. G.; Carder, D. R.; Symons, I. F.; Transport and Road Research Laboratory (Great Britain) (Crowthorne, Berkshire : Transport and Road Research laboratory, 1991)
09